The Effect of Work Discipline, Work Competence, and Work Motivation on Employee Performance at PT. BPR Karuna Ramanda Sejahtera Denpasar Barat - Putra, Kadek Dwi Udayana; Sapta, I Ketut Setia; Suryani, Ni Nyoman (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
Work discipline, competence, and work motivation are important factors that influence employee performance in supporting the achievement of company goals. PT. BPR Karuna Ramanda Sejahtera, as a financial institution, faces challenges in ensuring that employees are able to perform optimally. This study was conducted to analyze the influence of work discipline, competence, and work motivation on employee performance in the company. The results of this study are expected to provide strategic recommendations to improve overall employee performance. This study uses a quantitative method with a descriptive approach and multiple linear regression. The research sample consisted of 34 respondents, who were all employees of PT. BPR Karuna Ramanda Sejahtera, using a saturated sampling technique. Data were collected through a structured questionnaire that measured the variables of work discipline, competence, work motivation, and employee performance. Data processing was carried out using statistical analysis using the t-test and the coefficient of determination. The results show that work discipline, competence, and work motivation have a positive and significant effect on employee performance. Work motivation has the most dominant effect on employee performance. Based on these findings, it is recommended that companies increase employee rewards, provide additional training to improve competence, and improve discipline in terms of working hours. These efforts are expected to encourage increased productivity and more optimal performance in the future.